Ethnomedicine study of medicinal plants as malaria treatments in Moi Tribe, Southwest Papua, Indonesia - ANISA TRI HUTAMI; WIWIED EKASARI; MARCELLINO RUDYANTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hutami AT, Ekasari W, Rudyanto M. 2025. Ethnomedicine study of medicinal plants as malaria treatments in Moi Tribe, Southwest Papua, Indonesia. Biodiversitas 26: 1124-1134. Moi Tribe is the indigenous tribe in Sorong District and Raja Ampat of the Southwest Papua Province, Indonesia, that still holds onto their traditional value, including maintaining their health. Living in the eastern part of Indonesia, where malaria is still prevalent, the Moi Tribe still use the traditional method to treat their illness using medicinal herbs according to the knowledge that has been passed down from their ancestor. Ethnomedicine is a study of the perception and conception of a local tribe in order to understand health, or a study to investigate the traditional medical system of a tribal community. The purpose of this study was to gain information on the use of natural products by the Moi Tribe community in Kampung Malaumkarta, Sorong District to treat malaria. The qualitative research method was employed, with in-depth interviews, purposive, and snowball sampling. The inclusion and exclusion criteria qualified 30 people as informants. The study's results indicate that, depending on the route of administration, 10 single concoctions are administered orally, while two plants are administered topically. Based on the number of citations, the most widely used traditional antimalaria plants are the stems of tali kuning (Arcangelisia flava) with 0.96 RFC (Relative Frequency of Citation) index, papaya leaf (Carica papaya) with 0.7 RFC, and leaf of Orthosiphon aristatus with 0.26 RFC. The most common mode of preparation of the herbal medicines is to boil them in two glasses of water, strain them, and drink the decoction. They usually consume a glass of the concoction twice a day until the condition improves, which typically takes two days. The topical treatments include the use of itchy leaves (Laportea decumana) that are rubbed onto the body part that feels sore, leaf of Premna serratifolia is rubbed on the forehead to relieve headaches. Most of the plants that are used by the tribe have been shown to have various pharmacological effects.